Theorem znpnpcan2 | index | src |

theorem znpnpcan2 (a b c: nat): $ a + b -ZN (a + c) = b -ZN c $;
StepHypRefExpression
1 zneqb
a + b -ZN (a + c) = b -ZN c <-> a + b + c = b + (a + c)
2 eqtr
a + b + c = a + (b + c) -> a + (b + c) = b + (a + c) -> a + b + c = b + (a + c)
3 addass
a + b + c = a + (b + c)
4 2, 3 ax_mp
a + (b + c) = b + (a + c) -> a + b + c = b + (a + c)
5 addlass
a + (b + c) = b + (a + c)
6 4, 5 ax_mp
a + b + c = b + (a + c)
7 1, 6 mpbir
a + b -ZN (a + c) = b -ZN c

Axiom use

axs_prop_calc (ax_1, ax_2, ax_3, ax_mp, itru), axs_pred_calc (ax_gen, ax_4, ax_5, ax_6, ax_7, ax_10, ax_11, ax_12), axs_set (elab, ax_8), axs_the (theid, the0), axs_peano (peano1, peano2, peano5, addeq, muleq, add0, addS, mul0, mulS)